KORELASI ANTARA KONSUMSI ALKOHOL DAN FRACTIONAL URIC ACID CLEARANCE (FUAC) PADA POPULASI SUKU BALI DI DESA PENGLIPURAN, KUBU, BANGLI - Rama Putra, I Made; Raka Putra, Tjokorda (journal of internal medicine; Vol. 11, No. 3 September 2010, 2012)
Hyperuricemia is a term for serum uric acid (UA) level above normal limit, cause by overproduction or underexcretion. Fractional Uric Acid Clearance (FUAC) can determine both conditions. One of many factors affect to FUAC is alcohol. A cross sectional analytic study perform on Balinesse people in Penglipuran Village, to know correlation between alcohol consumption and FUAC. We arrange a questionaire with anthropometric data, physical and laboratory examinations, to collect data on September 2009. Blood and urine examinations perform in Laboratorium Klinik Prodia Denpasar. Data was analyzed by computer software, result in charactericstic descriptions, Kolmogorov-Smirnov tests for data normality, Spearman!s correlation to analyze dependent variable and independent variable, and multiple linear analysis, with 95% conÞ dent interval (CI) and signiÞ cance value p < 0.05. Ninety people fulÞ lled inclusions criteria, consist of 30 (33.3 %) female and 60 (66.7%) male. Mean age was 42.40 ± 13.91 years, mean UA serum were 5.19 ± 1.40 mg/dl, with 79 people (88.9 %) normouricemia and 11 people (11.1 %) hyperuricemia. Alcohol consumption prevalence was 47.8%. Mean FUAC were 7.92 ± 2.97%. Spearman!s correlation coeÞ cients (r) were -0.24; p = 0.02 between alcohol consumption and FUAC, while Ancova multivariate result none of variable signiÞ cant to FUAC, but alcohol consumption. In conclusion, there is a signiÞ cant correlation between alcohol consumption and FUAC.
Keywords: hyperuricemia, alcohol consumption, fractional uric acid clearance